Evaluation of ascitic soluble human leukocyte antigen-G for distinguishing malignant ascites from benign ascites - Juan Sun; Yan-Xiang Chang; Chun-Yan Niu (Tumor Biology)
The overexpression of soluble human leukocyte antigen-G is associated with malignant tumours. The purpose of our study was to detect soluble human leukocyte antigen-G concentrations in ascites and to evaluate the value of ascitic soluble human leukocyte antigen-G for the diagnosis of malignant ascites. Enzyme-linked immunosorbent assay was used to detect soluble human leukocyte antigen-G levels in 64 patients with malignant ascites and 30 patients with benign ascites. Receiver operating characteristic curves were used to evaluate the diagnostic efficacy of ascitic soluble human leukocyte antigen-G for the detection of malignant ascites. Ascitic soluble human leukocyte antigen-G levels were significantly higher in the malignant ascites group than in the benign ascites group (20.718 ± 3.215 versus 12.467 ± 3.678 µg/L, t = 7.425, p  < 0.001). The area under the receiver operating characteristic curve for ascitic soluble human leukocyte antigen-G was 0.957 (95% confidence interval, 0.872–0.992). At a cut-off value of 19.60 µg/L, the sensitivity and specificity of ascitic soluble human leukocyte antigen-G were 87.5% (95% confidence interval, 71.0%–96.5%) and 100% (95% confidence interval, 88.4%–100%), respectively. With respect to area under the receiver operating characteristic curve, sensitivity and specificity, ascitic carcinoembryonic antigen (0.810, 68.75% and 83.33%, respectively) and carbohydrate antigen 19-9 (0.710, 65.63% and 70%, respectively) significantly differed (all p  < 0.05). In malignant ascites that were cytology-negative and biopsy-positive, the rate of positivity for ascitic soluble human leukocyte antigen-G was 75%, which was higher than the corresponding rates for ascitic carcinoembryonic antigen (31.25%) and carbohydrate antigen 19-9 (6.25%; both p  < 0.05). In conclusion, The detection of ascitic soluble human leukocyte antigen-G exhibited good performance for diagnosing malignant ascites, and particularly those that were cytology-negative and biopsy-positive.